Development of ludico pedagogical activities through the usage of ICTs with the purpose of strengthening skills of a foreign language (2016)
One of the main objectives of Colombia´s current government is to improve the educational system of the country adapting it to current and future demands of the world, for that reason, the national government is developing proposals such as Colombia "very well" which is focused in teaching English as a foreign language in different educational institutions of the country. Besides this, due to the large development and technological advancement in the world, the national government is carrying out the project "plan decenal de education" which consist on providing technological tools such as tables, computers, internet etc. to public institutions of the country in order to familiarize young people with the technological demands of today's world, therefore they are more qualified to compete towards the existing requirements of the job´s world now. This project aims to make use of different technological tools for teaching English in seventh grade in order to strengthen the oral competition.